Characterization of two-phase combustible mixtures produced in a fan stirred bomb - Atzler, F.; Lawes, M.; Lee, Y.; Marquez, N. (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
The study of spray combustion is difficult due to the multiplicity of inter-dependent variables, such as pressure, temperature, droplet size, droplet size distribution, etc, especially industrial cases. Therefore, a combustion vessel developed to study the combustion of droplet clouds from a fundamental point of view has been chosen for the present work. However, it was required a full characterization of the aerosols produced before any combustion study could be undertaken. The distribution of droplets within the mixture, with out combustion, was characterised using several laser diagnostics, variables such as Sauter mean diameter, number density, gas and liquid equivalence ratios were determined. Nearly mono-sized droplet clouds were obtained in this vessel and the droplet diameter was a well defined function of time.